PENGARUH PENYALAHGUNAAN NARKOTIKA OLEH REMAJA TERHADAP TINGKAT KRIMINALITAS DI LINGKUNGAN SOSIAL - Alexander, Puguh Septian Alexander; Muhamad Chaidar (Jurnal Hukum to-ra : Hukum Untuk Mengatur dan Melindungi Masyarakat, 2025)
Narcotics abuse among adolescents in Indonesia has become an alarming and escalating social problem. This condition has serious impacts, not only on physical and mental health , but also has a close relationship with the increase in deviant behavior and criminal acts in society. This research aims to analyze the influence of narcotics abuse by adolescents on the criminality rate in the social environment. Based on the analysis, it was found that narcotics abuse often leads to unlawful acts such as theft, robbery, and violence. These actions are driven by various motives, including the economic need to buy drugs, as well as the loss of self-control and rational thinking abilities due to addictive substances. The results identified causal factors divided into internal and external. Internal factors include uncontrolled emotions , high curiosity , and submissiveness (inability to refuse peers). External factors include a lack of parental attention and negative influences from the social environment.